Vietnamese Diplomacy, 1975-2015: From Member of the Socialist Camp to Proactive International Integration - Thayer, Carlyle A (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
This article presents an overview of the evolution of Vietnamese foreign policy from national reunification in 1975 to the present. This forty-year timeframe is sub-divided into three parts. The first part traces Vietnam’s shift from a member of the socialist community led by the Soviet Union to a member of the international community from 1975-91. The second part reviews the implementation of Vietnam’s foreign policy of ‘multilateralizing and diversifying’ its external relations and becoming ‘a friend and reliable partner’ to all countries during the period 1991-2005. The third part considers developments after 2005 when Vietnam forged strategic partnerships with the major powers and key European and Southeast Asian states and proactively integrated with the global economic system. In summary, Vietnam’s foreign policy has contributed to safeguarding its sovereignty and national independence and contributed to national development and international integration.